Geography of the Family - Konrad, Kai A; Künemund, Harald; Lommerud, Kjell Erik; Robledo, Julio R (American Economic Review, 2002)
We study the residential choice of siblings who are altruistic towards their parents. The first-born child’s location choice influences the behavior of the second-born child and can shift some of the burden of providing care for the parents from one child to the other. These strategic considerations lead to an equilibrium location pattern with firstborn children locating further away from their parents than second-born children. We also analyze the location choices empirically using German data. These data confirm our theoretical predictions.